Detecting Sleep Apnea with Smart-tech: Scientific Breakthrough or Overhyped Technology? - Głowacka, Aleksandra; Grzeszczuk, Paulina; Skorulska, Iwona; Kalisz, Agnieszka; Ignatiuk-Chilkiewicz, Marta; Grywińska, Weronika; Kozakiewicz, Julia; Kościelecki, Kamil; Mączewska, Klaudia; Długozima, Patrycja (Quality in Sport, 2025)
Introduction: This review paper seeks to examine the existing knowledge on the underlying mechanisms of sleep apnea, the complexities associated with its diagnosis, and the potential of cutting-edge wearable technology to enhance its detection. Materials and Methods: A comprehensive review of the literature was conducted using the PubMed and Google Scholar databases using the following keywords: “Sleep apnea”, “Sleep disorder”, “Smart-tech”, “Smartwatch”, “Apnea treatment”, “Apnea monitoring”. Summary: Sleep plays a pivotal role in maintaining both physical and mental well-being. Sleep disorders can severely impair cognitive functions such as concentration and memory, while also leading to chronic fatigue and emotional instability. One of the most prevalent conditions is obstructive sleep apnea, characterized by recurrent interruptions in breathing during sleep, which, if left untreated, may result in serious health complications. Diagnosing and monitoring sleep apnea remains a challenge due to the shortage of specialized sleep laboratories. The integration of smart technology wearables has the potential to usher in a new era in the diagnosis and management of sleep apnea, along with the associated health complications. Conclusions: Advanced sleep monitoring technologies, ranging from traditional polysomnography to modern wearables and contactless systems, enable precise assessment of sleep disorders by continuously tracking key physiological parameters. An effective system must accurately differentiate between apnea types, assess severity using the apnea-hypopnea index (AHI), and analyze factors like body position to provide tailored treatment recommendations. Extending sleep monitoring beyond single-night laboratory studies to long-term home-based tracking enhances diagnostic accuracy, optimizes treatment strategies, and improves overall sleep health.